Aplikasi Stimulus Motoric Oral Massage terhadap Kemampuan Minum pada Bayi Prematur di Ruangan Perinatologi - Fristalia, Mikaela D.; Inayah, Iin; Nurjanah, Nunung; Mediani, Henny Suzana; Wulandari, Sri (Journal of Telenursing (JOTING), 2024)
This study aim to explore the effect of the motor stimulus oral massage to the ability to drink in premature baby in the Perinatology. This study was a quasi - experimental research by using the approach of pre and post test with control group design. The results showed that the difference between the pre-test and post-test scores obtained was 0.001. In conclusion, the application of motoric oral massage stimulus on the ability to drink in premature infants can improve the ability to drink in premature infants. Keyword: Drink Ability, Motoric Oral Massage Stimulus, Premature Baby